(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The study aimed at developing an educational unit from the National Education book for the seventh grade in the light of national values and measuring its effectiveness in the development of citizenship.The study sample consisted of (52) students from Hawar Secondary School for Girls and Boys and Tugbul Primary School for Girls and Boys.To achieve the objectives of the study, the content of the book was analyzed, the chosen educational unit was developed and the measure of citizenship behavior was reviewed.The results of the study showed that the concepts of national unity related to the political domain came first, followed by the social domain and the concepts of the economic domain came at the last position.The results also indicated that there were significant differences attributed to gender in favor of the female category.